NANOSPONGE DRUG DELIVERY SYSTEM: REVIEW - Gailany Ismael abed (Scholar Express Journals, 2021)
Drug delivery for a long time has been a major problem in the pharmaceutical field. The development of a new Nano-carrier system called nanosponge has shown the potential to solve the problem. Nanosponge has a porous structure and can entrap the drug in it. It can carry both hydrophilic and hydrophobic drugs. They also provide controlled release of the drugs and can also protect various substances from degradation. Nanosponge can increase the solubility of drugs and can also be formulated into an oral, topical and parenteral dosage form. The current review explores different preparation techniques, characterization parameters, as well as various applications of nanosponge.
Keywords: Drug; Nanosponge; preparation techniques; characterization parameters